2015
DOI: 10.1063/1.4922586
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared to ultraviolet optical properties of InSb grown on GaAs by molecular beam epitaxy

Abstract: Articles you may be interested inOptical properties of Si-doped and Be-doped InAlAs lattice-matched to InP grown by molecular beam epitaxy J. Appl. Phys. 114, 103504 (2013); 10.1063/1.4820519 Control of asymmetric strain relaxation in InGaAs grown by molecular-beam epitaxy J. Appl. Phys. 107, 103530 (2010); 10.1063/1.3361533 Microstructural improvements of InP on GaAs (001) grown by molecular beam epitaxy by in situ hydrogenation and postgrowth annealing Appl. Phys. Lett. 94, 041919 (2009); 10.1063/1.3077610 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…erefore, Figure 6 shows the peaks those are the highenergy-state transitions of the InSb lm and none of GaAs substrate. D'Costa et al [15] reported the SE study at room temperature for an InSb/GaAs grown by molecular beam epitaxy, showing similar critical energy points from InSb.…”
Section: Further Analyses and Temperature-dependent Sementioning
confidence: 84%
See 1 more Smart Citation
“…erefore, Figure 6 shows the peaks those are the highenergy-state transitions of the InSb lm and none of GaAs substrate. D'Costa et al [15] reported the SE study at room temperature for an InSb/GaAs grown by molecular beam epitaxy, showing similar critical energy points from InSb.…”
Section: Further Analyses and Temperature-dependent Sementioning
confidence: 84%
“…While CdTe is the only semiinsulating lattice-matched substrate available for InSb growth, it is difficult, however, to avoid the formation of the In 2 Te 3 precipitates at the InSb/CdTe interface [43,44]. Hence, many alternative materials (viz., Si, GaAs, InP, sapphire, and mica) have been chosen as substrates for preparing InSb epifilms [2,[15][16][17][19][20][21][22][23][24][25][26][27][28][29][30][31][32] by molecular beam epitaxy, liquid-phase epitaxy [18,30], metalorganic chemical vapor deposition (MOCVD) [20][21][22]31], metalorganic magnetron sputtering [32,45], and two-step growth process [46] methods. Despite a large (14.6%) lattice mismatch between InSb and GaAs, the semi-insulating GaAs is considered as an attractive substrate due to high chemical stability and resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…The most common way to effectively solve the above problem is to introduce some semiconductor materials which have small bandgap or adjustable, high mobility, fast response, and so on, to achieve a silicon compound semiconductor heterojunction photodetector with a large detection range and the high-speed response. Common traditional semiconductor materials include cadmium sulfide (CdS) [3], lead sulfide (PbS) [4], indium antimonide (InSb) [5,6], indium arsenide (InAs) [7], mercury telluride (HgCdTe) [8], etc. Besides, with the development of the epitaxial technology, such as molecular beam epitaxy technology (MBE) [6], metal organic chemical vapor deposition (MOCVD) [9], magnetron sputtering, organic synthesis and so on, heterogeneous structures can be made directly on top of silicon based on traditional silicon technology, which expands the potential applications of silicon in the field of optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…Common traditional semiconductor materials include cadmium sulfide (CdS) [3], lead sulfide (PbS) [4], indium antimonide (InSb) [5,6], indium arsenide (InAs) [7], mercury telluride (HgCdTe) [8], etc. Besides, with the development of the epitaxial technology, such as molecular beam epitaxy technology (MBE) [6], metal organic chemical vapor deposition (MOCVD) [9], magnetron sputtering, organic synthesis and so on, heterogeneous structures can be made directly on top of silicon based on traditional silicon technology, which expands the potential applications of silicon in the field of optoelectronics. Indium antimonide, as a typical Ⅲ-Ⅴ compound semiconductor material, has the highest electron mobility (78000 cm 2 V -1 s -1 at 300K), the narrowest direct bandgap (0.17 eV at 300K and 0.23 eV at 80K) and the smallest effective mass, which is a better choice here [10,11].…”
Section: Introductionmentioning
confidence: 99%